The Visigoths in Gaul and Iberia (update) - Ferreiro, Alberto.
1 online resource.
Keywords: The bibliography includes material published from 2013 to 2015. Following on from the first bibliography (Brill, 1988) and its updates (Brill 2006, 2008, 2011, 2014) this volume covers recent literature on: Archaeology, Liturgy, Monasticism, Iberian-Gallic Patristics, Paleography, Linguistics, Germanic and Muslim Invasions, and more. In addition, peoples such as the Vandals, Sueves, Basques, Alans and Byzantines are included. The book contains author and subject indexes and is extensively cross-indexed for easy consultation. A periodicals index of hundreds of journals accompanies the volume.